The RANKL-RANK Axis: A Bone to Thymus Round Trip - Sobacchi, Cristina; Menale, Ciro; Villa, Anna (Frontiers in Immunology, 2019)
The identification of Receptor activator of nuclear factor kappa B ligand (RANKL) and its cognate receptor RANK during a search for novel tumor necrosis factor receptor (TNFR) superfamily members has dramatically changed the scenario of bone biology by providing the functional and biochemical proof that RANKL signaling via RANK is the master factor for osteoclastogenesis. In parallel, two independent studies reported the identification of mouse RANKL on activated T cells and of a ligand for osteoprotegerin on a murine bone marrow-derived stromal cell line. After these seminal findings, accumulating data indicated RANKL and RANK not only as essential players for the development and activation of osteoclasts, but also for the correct differentiation of medullary thymic epithelial cells (mTECs) that act as mediators of the central tolerance process by which self-reactive T cells are eliminated while regulatory T cells are generated. In light of the RANKL-RANK multi-task function, an antibody targeting this pathway, denosumab, is now commonly used in the therapy of bone loss diseases including chronic inflammatory bone disorders and osteolytic bone metastases; furthermore, preclinical data support the therapeutic application of denosumab in the framework of a broader spectrum of tumors. Here, we discuss advances in cellular and molecular mechanisms elicited by RANKL-RANK pathway in the bone and thymus, and the extent to which its inhibition or augmentation can be translated in the clinical arena